SIGI 2019 Global Report Transforming Challenges into Opportunities (Social Institutions and Gender Index, 2019)
Over the past decade, the Social Institutions and Gender Index (SIGI) has consistently shown that governments need to look at discriminatory laws, social norms and practices to achieve gender equality and promote women's empowerment. This 2019 global report provides an overview of the main outcomes of the SIGI in relation to women and the family, their physical integrity, access to productive and financial resources and their civic rights. Building on these outcomes, this report provides a set of policy recommendations to enhance governments' efforts to deliver their gender-equality commitments through a three-pronged approach: starting with legal reforms and transformative gender policies, enforcing laws through community mobilisation and empowerment, and learning about the efficiency of policy through monitoring